2013
DOI: 10.1371/journal.pone.0074904
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of and Factors Associated with the Use of Smoking Cessation Medication in Korea: Trend between 2005–2011

Abstract: BackgroundIn Korea, nicotine replacement therapy (NRT) has been widely used in government-led, public health center-based smoking cessation services since 2004 and varenicline has become available from 2007 but without reimbursement. In this study which used a series of nationwide cross-sectional surveys in Korea performed from 2005 to 2011, we examined the prevalence of smoking cessation medication use and factors associated with it.MethodsWe analyzed data from the third to fifth waves of Korean National Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
6
1
Order By: Relevance
“…Although a diagnosis of cancer has been regarded as a ‘teachable moment’ to change the detrimental behaviors of patients and their family members, almost a quarter of our patients and majority of family members reported that they continued smoking for at least 1 month after their diagnosis. While the prevalence of continued smoking in our cancer patient sample (45/990 = 4.5%) is much lower than the reported prevalence in Korea (around 25% in adult population) , that of patients' family (151/990 = 15.3%) was not very different from that of the general population considering the older age and female predominance of our family sample. Continued smoking by patients is especially problematic because it is associated with a poor response to cancer treatment, increased risk of recurrence and secondary cancer, and mortality , and continued smoking by family members is also problematic because it increases the risk of exposure to secondhand smoke, access to cigarettes, and the difficulty of cessation for patients .…”
Section: Discussioncontrasting
confidence: 82%
“…Although a diagnosis of cancer has been regarded as a ‘teachable moment’ to change the detrimental behaviors of patients and their family members, almost a quarter of our patients and majority of family members reported that they continued smoking for at least 1 month after their diagnosis. While the prevalence of continued smoking in our cancer patient sample (45/990 = 4.5%) is much lower than the reported prevalence in Korea (around 25% in adult population) , that of patients' family (151/990 = 15.3%) was not very different from that of the general population considering the older age and female predominance of our family sample. Continued smoking by patients is especially problematic because it is associated with a poor response to cancer treatment, increased risk of recurrence and secondary cancer, and mortality , and continued smoking by family members is also problematic because it increases the risk of exposure to secondhand smoke, access to cigarettes, and the difficulty of cessation for patients .…”
Section: Discussioncontrasting
confidence: 82%
“…12 13 It continues to attract attention from researchers and practitioners alike. [14][15][16][17][18][19] Several studies have investigated how much the introduction of varenicline has led to an increase in the overall use of pharmacotherapy. These studies differ in sample size and in methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding co-morbid features, disordered gamblers in the financial market were less likely to smoke cigarettes compared with disordered horse race gamblers, although the 51% among the financial markets is higher than the national average of 25.4% based on a nationwide survey on the prevalence of smoking in Korea in 2011 ( Shin et al., 2013 ). Cigarette smoking is also derived from multiple causes such as socio-environmental, psychological and biological factors.…”
Section: Discussionmentioning
confidence: 99%